'Hard hearts' resounding now: anatomising race, resistance, and community in The Merchant in Venice (2016) and Julius Caesar (2017). Issue 1 (July 2019) - Henderson, Diana E
Placing two innovative, high-profile stagings of Shakespeare in dialogue, this essay emphasises the power of re-citations, both as aural echoes and as tableaux, across dramatic genres. Building on Martin Luther King's self-quotation within his anti-Vietnam address, it reveals how the Compagnia de' Colombari's site-specific The Merchant of Venice, performed in the originary Jewish Ghetto, and the New York Public Theater's Julius Caesar, which created a national furore, each employed non-traditional casting and Shakespeare's Act 4 emphasis on threatened yet suspended male-on-male violence to create complex political theatre, addressing historical ethnic and racial inequalities within 'the fierce urgency of now'.